2014
DOI: 10.1088/1674-4926/35/11/114002
|View full text |Cite
|
Sign up to set email alerts
|

Comparative study of leakage power in CNTFET over MOSFET device

Abstract: A comparison of the CNTFET device with the MOSFET device in the nanometer regime is reported. The characteristics of both devices are observed as varying the oxide thickness. Thereafter, we have analyzed the effect of the chiral vector and the temperature on the threshold voltage of the CNTFET device. After simulation on the HSPICE tool, we observed that the high threshold voltage can be achieved at a low chiral vector pair. It is also observed that the effect of temperature on the threshold voltage of the CNT… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
18
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(19 citation statements)
references
References 20 publications
1
18
0
Order By: Relevance
“…The performance of CMOS and CNFET based inverter and NAND/NOR logic circuits have been analyzed for different gate dielectric materials. Various dielectric materials considered are silicon nitride (Si 3 N 4 ), Aluminum oxide (Al 2 O 3 ), Hafnium oxide (HfO 2 ) and Zirconium oxide (ZrO 2 ) having dielectric constant 7.5, 9, 15.6 and 19 respectively [22]. Table 2 lists the delay, power dissipation and power-delay product for CMOS and CNFET based inverter circuit.…”
Section: Simulations and Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The performance of CMOS and CNFET based inverter and NAND/NOR logic circuits have been analyzed for different gate dielectric materials. Various dielectric materials considered are silicon nitride (Si 3 N 4 ), Aluminum oxide (Al 2 O 3 ), Hafnium oxide (HfO 2 ) and Zirconium oxide (ZrO 2 ) having dielectric constant 7.5, 9, 15.6 and 19 respectively [22]. Table 2 lists the delay, power dissipation and power-delay product for CMOS and CNFET based inverter circuit.…”
Section: Simulations and Resultsmentioning
confidence: 99%
“…A. Singh et al analyzed the performance of CNFET for low power applications, high I ON /I OFF ratio, sharp sub-threshold slope, high transconductance in CNFETs show that it is a promising device to be used at nanoscale [21]. S. K. Sinha et al studied the comparison of leakage power in CNFET and MOSFET, it was observed that threshold voltage (V TH ) varies sharply in MOSFET at high temperature (t > 150℃) whereas in CNFET temperature has negligible effect on V TH [22].…”
Section: Related Workmentioning
confidence: 99%
See 1 more Smart Citation
“…CNFETs are the transistors in which number of carbon nanotubes (CNTs) acts as a physical channel between source and drain unlike virtual channel in case of metal oxide semiconductor field effect transistor (MOSFET) [8]. CNTs are thin sheets of graphene.…”
Section: Carbon Nanotube Field Effect Transistormentioning
confidence: 99%
“…In most of the modern design is based on Carbon nanotube because of its superior properties in terms of power consumption, leakage power, delay. The quantum capacitance has a significant force in nanoscale device [6]. The CNTFET-based 8T SRAM cell demonstrates that it provides high stability, low delay and low power, which is better than CNTFET-based 6T SRAM cell as well as CMOS SRAM cell was addressed in [7].…”
Section: Introductionmentioning
confidence: 99%